2018
DOI: 10.1107/s2052520618008442
|View full text |Cite
|
Sign up to set email alerts
|

High-density HNIW/TNT cocrystal synthesized using a green chemical method

Abstract: HNIW/TNT cocrystals are synthesized by a new chemical method. The performance of the cocrystals is improved from previous preparation techniques and this new method is a more environmentally friendly approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Thus, a co-crystal is a new crystal constituted by two or more chemical elements with a proper stoichiometric ratio linked with hydrogen bonding, van der Waals forces, p-p stacking and p-p stacking, and/or other non-covalent interactions. [17][18][19] Several energetic co-crystals with interesting features have been developed so far and the topic continues to attract current/future and increasingly intense international discussion to fulll the requirement of the next generation of EMs. [20][21][22] As one of the most interesting propellant oxidizer and explosive ingredient, AN displays prominent characteristics such a positive oxygen balance, low cost, availability, and 100% of gaseous decomposition products.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a co-crystal is a new crystal constituted by two or more chemical elements with a proper stoichiometric ratio linked with hydrogen bonding, van der Waals forces, p-p stacking and p-p stacking, and/or other non-covalent interactions. [17][18][19] Several energetic co-crystals with interesting features have been developed so far and the topic continues to attract current/future and increasingly intense international discussion to fulll the requirement of the next generation of EMs. [20][21][22] As one of the most interesting propellant oxidizer and explosive ingredient, AN displays prominent characteristics such a positive oxygen balance, low cost, availability, and 100% of gaseous decomposition products.…”
Section: Introductionmentioning
confidence: 99%
“…Solvent-assisted grinding is an environmentally friendly method; however, it is difficult to control the cocrystals’ morphologies [ 43 ]. L. Yan et al reported an energetic cocrystal (HNIW/TNT) synthesis using a solvent-assisted grinding method [ 47 ]. In their work, they used ethanol as a solvent due to its environmentally friendly nature.…”
Section: New Energetic Cocrystalsmentioning
confidence: 99%
“…Recently, many studies [49][50][51] on development of co-crystals, such as a co-crystal composed of hydrazine 3-nitro-1,2,4-triazol-5-one (HNTO) and ammonium nitrate (AN). This co-crystal was developed in order to overcome some of the drawbacks (i.e., high hygroscopicity and phase transitions of AN and negative oxygen balance of HNTO) of AN and HNTO [49].…”
Section: Novel Oxidizing Agentsmentioning
confidence: 99%